The Tao of Gung Fu : A Study in the Way of Chinese Martial Art - Lee, Bruce; Edited By Little, John (Boston Charales E. Tuttle Co., 1997)
This is the book that Bruce Lee had intended to publish as an in-depth follow up to his Chinese Gung Fu. Prior to his death, he had written the majority of the text, which explores such topics as yin-yang as it applies to martial arts, Eastern and Western fitness methodologies, and studies of martial arts and self-defense techniques. Also included is Bruce Lee's Gung Fu "scrapbook" of anecdotes on the histories and traditions of the various martial arts of China. The manuscript was completed and edited by martial arts expert John Little in cooperation with the Bruce Lee Estate.
Include Appendix and Colored Illustrations.
Keywords: Lee, Bruce, 1940-1973 -- Kung Fu